Correlations between smartphone addiction and alexithymia, attachment style, and subjective well-being: A meta-analysis - Ding, Yueming; Huang, Haitao; Zhang, Yiming; Peng, Qianwen; Yu, Jingfen; Lu, Guangli; Wu, Huifang; Chen, Chaoran (Frontiers in Psychology, 2022)
Background: Smartphone addiction (SA) has become a social problem that affects peoples’ quality of life and is frequently reported to be correlated with alexithymia, avoidant or anxious attachment styles, and subjective well-being. This study aimed to investigate the relationship between SA and alexithymia, attachment style, and subjective well-being. Methods: A meta-analysis was conducted following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. The following electronic databases were searched: PubMed, Web of Science, Embase, PsycINFO, PsycArticles, China National Knowledge Infrastructure (CNKI), WANFANG DATA, and Chongqing VIP Information Co., Ltd. (VIP). Stata 16.0 was used to analyse the overall effect and test the moderating effect. Results: One hundred and ten studies were included, involving a total of 96680 participants. SA had a significantly high positive correlation with alexithymia (r = 0.40), attachment anxiety (r = 0.37), and negative emotions (r = 0.31), and a low positive correlation with attachment avoidance (r = 0.17). In addition, there was a high negative correlation between SA and subjective well-being (r = -0.33) and a low negative correlation between SA, life satisfaction (r = -0.17), and positive emotions (r = -0.18). A moderation analysis revealed that age significantly moderated the relationship between SA and positive emotions. The tools for measuring SA significantly moderated the relationship between SA, alexithymia, attachment anxiety, and subjective well-being. Meanwhile, subjective well-being measurement tools significantly moderated the relationships between SA, subjective well-being, and negative emotions. Conclusion: SA was closely related to alexithymia, attachment style, and subjective well-being. In the future, longitudinal research can be conducted to better investigate the dynamic changes in the relationship between them.